2023
DOI: 10.3390/children10071192
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Neonatal Hyperbilirubinemia and the Role of Fenofibrate as an Adjuvant to Phototherapy

Abstract: Background: One of the most prevalent illnesses in neonates that needs care and treatment is neonatal jaundice. Several drugs are used as pharmacological modalities for treating hyperbilirubinemia, like intravenous immunoglobulin, D-penicillamine, metalloporphyrin, phenobarbital, zinc sulfate and clofibrate. Previous studies suggest the usefulness of fenofibrate in the treatment of hyperbilirubinemia. Objectives: The study aims at assessing the effectiveness of oral fenofibrate in the treatment of indirect neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In a recent study, authors reported that combining conventional phototherapy with a single oral dose of 10 mg/kg fenofibrate may shorten the time it takes to lower the bilirubin levels. This supports an effect of fenofibrate as an adjuvant therapy to phototherapy in neonates that may shorten length of phototherapy and accelerate discharge from the hospital [100].…”
Section: Fibratesupporting
confidence: 59%
“…In a recent study, authors reported that combining conventional phototherapy with a single oral dose of 10 mg/kg fenofibrate may shorten the time it takes to lower the bilirubin levels. This supports an effect of fenofibrate as an adjuvant therapy to phototherapy in neonates that may shorten length of phototherapy and accelerate discharge from the hospital [100].…”
Section: Fibratesupporting
confidence: 59%
“…New treatments for neonatal jaundice help clear bilirubin faster, reduce phototherapy time and lower the need for exchange transfusions. Practices such as infant massage, 26 and medications such as fenofibrate, 27 zinc sulphate, 28 and ursodeoxycholic acid 29 can help, although some may need a few days to show benefit. High costs and limited or no utility to prevent bilirubin-induced neurological dysfunction may constrain use in RCS.…”
Section: Adjuvant Therapymentioning
confidence: 99%